Metabolic-Related Index to Predict Post-Transplantation Diabetes Mellitus After Kidney Transplantation - Xiaojie, Ni; Bicheng, Chen; Yongling, Li; Tingting, Huang; Yi, Zhou; Chen, Zimiao (Hormone and Metabolic Research, 2023)
Metabolic-related markers are novel tools for assessing insulin resistance. Early identification of post-transplantation diabetes mellitus (PTDM) before hyperglycemia can be helpful to attenuate the rapid development of diabetic complications. This article aims to explore the convenient and inexpensive values of metabolic-related markers, including TyG, TyG-BMI, TG/HDL-C, and non-HDL-C/HDL-C for predicting PTDM. The data of 191 kidney transplant recipients in our center were collected retrospectively. The association between TyG, TyG-BMI, TG/HDL-C, non-HDL-C/HDL-C and the risk of PTDM was examined by the area under the curve and logistic regression analyses. During 6 months follow-up, 12.04% of KT recipients developed PTDM, and significantly higher values of TyG-BMI, TyG, and non-HDL-C/HDL-C was found in patients with PTDM than in nondiabetic patients, especially among the recipients taking tacrolimus, regardless of gender. The incidence of PTDM increased along with the values of TyG or TyG-BMI. After adjusting for multiple potential factors, recipients with the highest trisector of TyG or TyG-BMI still had a higher risk of PTDM morbidity. In conclusion, TyG, TyG-BMI, TG/HDL-C and non-HDL-C/HDL-C can be used as cost-effective and promising monitors to identify individuals at high risk of PTDM, and TyG-BMI was the best alternative marker among the four markers.
Keywords: insulin resistance; post transplantation diabetes mellitus; triglyceride; triglyceride-glucose index